1982
DOI: 10.1128/jb.150.2.963-965.1982
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced genetic changes in dry yeast cells

Abstract: Cells of Saccharomyces cerevisiae were dried in vacuum, exposed to oxygen, nitrogen, air, and water vapor, and rehydrated with degassed medium without exposure to air. Drying per se caused few genetic changes, but the exposure of dry cells to oxygen increased the frequency of adenine-requiring colonies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, Pereira et al [17] demonstrated that yeast cells were oxidized more than 10-fold by desiccation. Desiccated organisms kept in a vacuum or a reduced oxygen environment such as nitrogen recovered well compared to those kept in normal air or oxygen environment, suggesting that exogenous oxidation is a damaging factor during anhydrobiosis [18][19][20]. On the other hand, there were two downregulated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pereira et al [17] demonstrated that yeast cells were oxidized more than 10-fold by desiccation. Desiccated organisms kept in a vacuum or a reduced oxygen environment such as nitrogen recovered well compared to those kept in normal air or oxygen environment, suggesting that exogenous oxidation is a damaging factor during anhydrobiosis [18][19][20]. On the other hand, there were two downregulated proteins.…”
Section: Discussionmentioning
confidence: 99%